2009
DOI: 10.1080/10413200903019376
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Dysmorphia Symptoms and Their Relationships to Self-concept and Negative Affect Among College Recreational Exercisers

Abstract: This study explored the nature of the relationship between muscle dysmorphia symptoms and self-concept as well as negative affect variables. Female (n = 183) and male (n = 103) college students completed a packet of questionnaires. Data were analyzed using canonical correlation analyses and revealed significant relationships between the sets of variables. Specifically, the variance explained by muscle dysmorphia symptoms in self-concept and negative affect variables was greater than the variance explained in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“… The total row numbers reflect the number of unique articles that used each reporting type. Because three articles (Cafri et al, ; Cella et al, ; Ebbeck, Watkins, Concepcion, Cardinal, & Hammermeister, ) used multiple measures, the total does not reflect the sum of the measures. …”
Section: Resultsmentioning
confidence: 99%
“… The total row numbers reflect the number of unique articles that used each reporting type. Because three articles (Cafri et al, ; Cella et al, ; Ebbeck, Watkins, Concepcion, Cardinal, & Hammermeister, ) used multiple measures, the total does not reflect the sum of the measures. …”
Section: Resultsmentioning
confidence: 99%
“…Dissatisfaction with musculature, resulting in feeling unacceptably small, is the main source of body-image disturbance in men (Pope et al, 2000). Similar to anorexia (Pope, Katz & Hudson, 1993), there is a positive predictive relationship between muscle dysmorphia and social physique anxiety (Ebbeck, Watkins, Concepcion, Cardinal & Hammermeister, 2009;Grieve, Jackson, Reece, Marklin & Delaney, 2008), depression (Ebbeck et al, 2009), and perfectionism (Kuennen & Waldren, 2007) and a negative predictive relationship with perceived body attractiveness (Ebbeck et al, 2009). Thus, our finding of a gender difference indicating that men who exercise to gain weight exhibit more exercise dependence symptoms than women who exercise to lose weight provides insight into relationships among gender, eating pathology, and compensatory behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Kanayama et al concluded that low self-esteem and MD would need to be present to motivate initiation of AAS use. Ebbeck, Watkins, Concepcion, Cardinal, and Hammermeister (2009) explains how selfesteem and MD may motivate AAS use. They maintain that men with low self-esteem often develop behaviours associated with MD (i.e., excessive weightlifting, muscle checking and body anxiety) to improve their body image, which in turn increases their self-esteem.…”
Section: Introductionmentioning
confidence: 99%